Turismo da terceira idade : lazer na natureza, em Sergipe - Félix, Janini de Oliveira (2018)
The aging of Brazilian population is a reality and it has been the object of many studies in the country, considering statistical data collected by Brazilian Institute of Geography and Statistics. The age pyramid scenario is an important subject to be included in discourses and public policies guidelines as well as private services as a way to improve service option for the elderly, a growing segment in society. This study aims to analyze public policies and tourism promotion related to the most visited natural attractions by old age tourists in Sergipe. Specific objectives are: 1. Describe the main tourist attractions that involve thematic leisure in nature and tourism for the elderly in Sergipe; 2. Evaluate public policies actions, which aim to boost tourism of natural attractions destinations in Sergipe. This research is restricted to one of the segments of consumers in tourism: people considered elderly, in accordance to Law nº 10.741, dated October 1, 2003. The methodological approach is deductive hypothetical and its procedures are the analysis of collected secondary data, bibliographic and documentary elements such as publications of technical documents, studies, and government planning reports. The studies showed a lack of major investments in the tourism sector that serves this niche. It also showed the misalignment between planning process and public management with the available tourist structure, although there is already governmental disclosure including Sergipe regions identified as tourist in the national tourist scenario.